Effect of different resistance elements in sesame root rot disease - Ali Altaee; Mohammed Ismail; Najwa Al-Lashi (College of Education for Pure Sciences, 2007)
Survey of the fields in Ninevah province indicated that Sesame root rot occurrence and severity were the highest at Hammam Al-Alil followed by Rabia and Al-Rashidia , these diseases were caused by Pythium aphanidermatum , Fusarium so/ani and Macrophomina phaseolina . The latter decreased seed production and oil content . The effect of pelleting the seeds with chemical and biocontrol elements was studied on the percent infection , root-rot severity and different growth features of the plants after three and four months of planting in the greenhouse . Pelleting the seeds with Beltanol and T. harzianum by using xanthan gave the least infection and root-rot severity in both periods . It also gave better plant growth features .